2021
DOI: 10.1186/s12929-020-00700-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and proteomic profiling revealed reprogramming of carbon metabolism in acetate-grown human pathogen Candida glabrata

Abstract: Background Emergence of Candida glabrata, which causes potential life-threatening invasive candidiasis, has been widely associated with high morbidity and mortality. In order to cause disease in vivo, a robust and highly efficient metabolic adaptation is crucial for the survival of this fungal pathogen in human host. In fact, reprogramming of the carbon metabolism is believed to be indispensable for phagocytosed C. glabrata within glucose deprivation condition during infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…These results indicated that WG-608 had considerably greater capability for essential amino acid biosynthesis. Consistent with our results, Wang Z. Y. et al (2021) and also found that the synthesis of amino acids (i.e., L-lysine, L-threonine and L-proline) was upregulated in the high ε-PL-producing strain Streptomyces diastatochromogenes 6#-7 . Additionally, other studies have shown that L-arginine levels contribute to the arginine deaminase pathway to enhance acid resistance, while high L-glutamate and L-proline levels promote cellular tolerance and acclimation to environmental extremes.…”
Section: Wg-608supporting
confidence: 92%
“…These results indicated that WG-608 had considerably greater capability for essential amino acid biosynthesis. Consistent with our results, Wang Z. Y. et al (2021) and also found that the synthesis of amino acids (i.e., L-lysine, L-threonine and L-proline) was upregulated in the high ε-PL-producing strain Streptomyces diastatochromogenes 6#-7 . Additionally, other studies have shown that L-arginine levels contribute to the arginine deaminase pathway to enhance acid resistance, while high L-glutamate and L-proline levels promote cellular tolerance and acclimation to environmental extremes.…”
Section: Wg-608supporting
confidence: 92%
“…SARS-CoV-2 gains access to cells via ACE2 receptor binding with TMPRSS2 priming [ 7 , 8 ]. The testes are reported to express ACE2, particularly in the spermatogonia, Leydig cells and Sertoli cells, which leads to the hypothesis of SARS-CoV-2 gaining access to testicular tissues and seminal fluid, directly affecting male reproductive health [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 virus gains access to human cells through binding to cellular angiotensin-converting enzyme 2 (ACE2) receptors via the receptor-binding domain as part of the spike (S) protein. This further requires priming by cellular transmembrane protease, serine 2 (TMPRSS2) [ 7 , 8 ]. Following infection through exposure to respiratory droplets, the incubation period is usually 3–7 days [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of antibiotic-loaded nano-formulations is considered a valid strategy for bacteria targeting because of its numerous advantages over conventional formulations, including improved stability, controlled antibiotic release, targeted capability, and increased bioavailability (Pant et al, 2021 ). Some issues, such as solubility, drug resistance, and epithelium permeation, can also be resolved by targeting pathogens of nanocarriers.…”
Section: Possible Drawbacks Of Nanocarriers For Antibioticsmentioning
confidence: 99%